ANALISIS WASTE MENGGUNAKAN METODE VALUE STREAM ANALYSIS TOOLS PADA PROYEK PEMBANGUNAN INSTALASI GAWAT DARURAT RSUD PIDIE JAYA - Sheragizca Yolanda Situmeanga; Muhammad Afifuddin; Hafnidar A. Rani (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Construction project is a long process activity where the researcher finds obstacles which cannot be separated from the used resources. Everything in the projects which may add the needed costs called by the term waste. In the project implementation of Regional Public Hospital (IGD) construction project in Pidie Jaya, there was a significant delay in the project schedule which could be caused by several things which may  lead the project into waste construction. This is the main reason why does the Value stream analysis tools (VALSAT) method was used during the research in order to identify the cause of occuring waste. This goal of this research is to identify the waste which potentially occure during the  Regional Public Hospital (IGD) project in Pidie Jaya. Besides, this research is also determine the grade and tool waste by using the VALSAT. Based on the literature review, there are 8 wate categories  which could be reviewed based on materials, labor and tools used during the project. The identified waste data are obtained by the interview conducted to 4 respondents and questionaire with 15 respondents and handed out to contratctors. Based on the result and data processing which using descriptive analysis, it can be concluded that the most influential waste on the project was waste waiting and waste overprocessing which obtain a value of 5 and cause the excessive effects on the project. Furthermore, the result of the grade analysis and tool waste determination by using the VALSAT method produced a process Acivity Mapping to analyze the occuring waste that occurs with a total score of 135.